Temporal trends, sources, and relationships between sediment characteristics and polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) in sediment cores from the major Seine estuary tributary, France. (November 2020) - Gardes, Thomas; Portet-Koltalo, Florence; Debret, Maxime; Humbert, Kevin; Levaillant, Romain; Simon, Michel; Copard, Yoann
Abstract: Temporal trends in polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) were reconstructed from sediment cores collected in the Martot and Les Damps ponds, downstream of the Eure River watershed. PAHs exhibited a positive correlation with fine fractions, but mainly with the refractory organic carbon measured in the sediments, which suggests PAH inputs from materials largely composed of refractory carbon (e.g. soot). Since around the 1940s, PAH concentrations ranged between 2.93–38.20 and 2.27–28.20 mg kg −1 in sediment cores from the Martot and Les Damps ponds, respectively. Based on the temporal distribution of isomers and diagnostic ratios, the PAHs in the sediments were found to be predominantly of pyrogenic origin, particularly in the 1940s–1960s, when PAH levels were particularly high. PCBs also showed an affinity with the fine fraction and with refractory organic carbon, albeit less so than PAHs. Since around the 1940s, PCB concentrations ranged between 0.02–1.57 in Martot Pond and 0.09–1.60 mg kg −1 in Les Damps Pond. The recorded PCB temporal trends were mainly associated with the production, consumption, and banning of these chemicals in France. According to the temporal distribution of PCB congeners, high levels in the 1950s–1970s were linked to "technical mixture" discharges into waterways, which were mainly composed of "low chlorinated congeners", whereas PCB levels after the 1970s were of atmospheric origin. Graphical abstract: Image 1 Highlights: Temporal trends of PAHs and PCBs were reconstructed from sediment cores. PAHs and PCBs showed a positive correlation with fine fractions. PAHs showed a positive correlation with the refractory organic carbon. PAHs were found to be predominantly of pyrogenic origin. High levels of PCBs were linked to technical mixture discharges into the river.